Shikonin induces ferroptosis in multiple myeloma via GOT1-mediated ferritinophagy - Li, Wenxia; Fu, Hangjie; Fang, Liuyuan; Chai, Hui; Gao, Tianwen; Chen, Zhenzhen; Qian, Shenxian (Frontiers in Oncology, 2022)
Multiple myeloma (MM) is an incurable hematological malignancy that lacks effective therapeutic interventions. Ferroptosis is a newly discovered form of cell death that has shown great potential for MM therapy. As a proteasome inhibitor and necroptosis inducer, shikonin (SHK) performs dual functions in MM cells. However, whether SHK inhibits the development of MM via ferroptosis or any other mechanism remains elusive. Here, we provide evidence that SHK treatment was capable of inducing ferroptosis and immunogenic cell death (ICD) in MM. The results showed that SHK treatment inhibited cell proliferation, induced lactate dehydrogenase release, triggered cell death, evoked oxidative stress, and enhanced ferrous iron levels. Furthermore, treatment with ferroptosis inhibitors reversed SHK-induced cell death, which indicated that ferroptosis contributed to this phenomenon. Meanwhile, ferroptosis was accompanied by the extracellular release of ATP and HMGB1, which are characteristics of ICD. Further investigation showed that glutamic-oxaloacetic transaminase 1 (GOT1) acted as a critical mediator of SHK-induced ferroptosis by promoting ferritinophagy. In conclusion, our findings suggest that SHK exerts ferroptotic effects on MM by regulating GOT1-mediated ferritinophagy. Thus, SHK is a potential therapeutic agent for MM.